Mapping the research landscape: a bibliometric analysis of organic food products and their marketing challenges - Sohana Sultana; Bikram Barman; Rashmi Singh; Praveen Koovalamkadu Velayudhan (Discover Sustainability)
Abstract Organic farming is a sustainable cultivation practice that emphasizes the use of natural inputs and processes for crop and livestock production, minimizing reliance on synthetic or chemical fertilizers, pesticides, and genetically modified organisms. The need for organic farming arises from the growing global concerns over environmental degradation, soil depletion, and the health risks associated with conventional farming methods. The organic farming market is an expanding niche in the global agricultural sector. This study conducted a bibliometric analysis of the marketing challenges of organic food products. By leveraging the Scopus database, a total of 1,538 relevant publications were identified and analysed using suitable bibliometric software tools. This method allows for the identification of research trends, influential authors, key topics, and the development of knowledge within the field. The analysis reveals a significant trend: despite the expanding interest in the challenges of marketing organic food products, there is a notable lack of collaboration among researchers and sources, as well as a limited range of documented studies. India, with the greatest number of organic farmers and the second-largest amount of organic farmland, has become a global leader in the organic industry. However, its particular prospects and problems are just now starting to be recognized. The results underline the need for better coordinated and cooperative research efforts, even if there has been a growth in research activity on this subject, underscoring India’s rising importance in the global organic market.